Simultaneous bilateral laparoscopic cortical-sparing adrenalectomy for bilateral pheochromocytomas in multiple endocrine neoplasia type 2 - Qi, Xiao-Ping; Lian, Bi-Jun; Fang, Xu-Dong; Dong, Fang; Li, Feng; Jin, Hang-Yang; Zhang, Ke; Wang, Kang-Er; Zhang, Yi (Frontiers in Surgery, 2023)
Purpose This study aimed to assess the feasibility of synchronous bilateral laparoscopic or open cortical-sparing adrenalectomy (SB-LCSA or SB-OCSA) for bilateral pheochromocytomas (bPHEOs) in multiple endocrine neoplasia type 2 (MEN2). Methods Altogether, 31 patients (54.8% were women) were diagnosed with MEN2-related bPHEOs, and 29 of them underwent varying specific adrenalectomies. We systematically analyzed and evaluated their clinical profiles, mutation types, tumor histopathological features, and follow-up records. Results All 31 patients with bPHEOs presented with RET-C634 (90.3%) and RET-M918T (9.7%) mutations, and the median age at initial presentation was 38 years (range, 23–78). bPHEOs were synchronous in 27 patients and metachronous in 4 (12.9%) patients. In total, 29 patients underwent initial cortical-sparing adrenalectomy (CSA) including 23 (79.3%) undergoing synchronous bilateral CSA (18 SB-LCSA and 5 SB-OCSA) and 6 (20.7%) undergoing metachronous CSA. SB-LCSA and synchronous surgery were associated with less bleeding volume and shorter length of hospital stay than SB-OCSA and metachronous surgery (all P’s < 0.05). Corticosteroid replacement treatment was necessary for 14 patients (45.2%) after bilateral CSA. During a median follow-up period of 7 years (range, 1.8–23), three of these patients (10.3%) had a recurrent disease that required reoperation. Conclusion SB-LCSA is feasible for treating synchronous bPHEOs and should be recommended as a prioritized surgical approach.